2017
DOI: 10.1002/1873-3468.12539
|View full text |Cite
|
Sign up to set email alerts
|

Thioesterase overexpression in Nicotiana benthamiana leaf increases the fatty acid flux into triacylgycerol

Abstract: Increasing the oil content of leafy biomass is emerging as a sustainable source of vegetable oil to meet global demand. Transient gene expression in leaf provides a reproducible platform to study the effect of transgenes on lipid biosynthesis. We first generated a transgenic Nicotiana benthamiana line containing high levels of triacylglycerol in the leaf tissue (31.4% by dry weight) by stably expressing WRI1, DGAT1 and OLEOSIN. We then used this line as a platform to test the effect of three Arabidopsis thalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In N. benthamiana, total lipids were extracted from leaf tissues using chloroform : methanol : 0.1 M KCl (2 : 1 : 1 v/v/v), as described by El Tahchy et al . (). TAG was fractionated by TLC (Silica gel 60; MERCK, http://www.merck.com) in hexane : diethylether : acetic acid (70 : 30 : 1 v/v/v), and visualized by spraying Primuline (5 mg/100 ml acetone : water, 80 : 20 v/v; Sigma‐Aldrich, https://www.sigmaaldrich.com) and exposing the plate to UV light.…”
Section: Methodsmentioning
confidence: 97%
“…In N. benthamiana, total lipids were extracted from leaf tissues using chloroform : methanol : 0.1 M KCl (2 : 1 : 1 v/v/v), as described by El Tahchy et al . (). TAG was fractionated by TLC (Silica gel 60; MERCK, http://www.merck.com) in hexane : diethylether : acetic acid (70 : 30 : 1 v/v/v), and visualized by spraying Primuline (5 mg/100 ml acetone : water, 80 : 20 v/v; Sigma‐Aldrich, https://www.sigmaaldrich.com) and exposing the plate to UV light.…”
Section: Methodsmentioning
confidence: 97%
“…Total lipid fraction (lower phase) was separated by 2 min centrifugation at 4000 × g, dried under nitrogen and resuspended in chloroform. Total lipid extracts were fractionated by thin layer chromatography fractionation as previously described , followed by fatty acid methyl ester quantification and analysis by gas chromatography, also conducted as previously described (Vanhercke et al, 2013;El Tahchy et al, 2017). Unless otherwise stated, analyses were conducted on a minimum of three individual samples for each genotype, condition or cell population.…”
Section: Lipid Extractions and Analysesmentioning
confidence: 99%
“…Pioneering studies have already demonstrated the power of such efficient transient transformation systems. For example, the "Leaf Oil" platform technology, which allows plants to accumulate oil in all vegetative organs with yields potentially exceeding those of canola and oil palm, was quickly developed thanks to an extensive number of design-built-test-learn cycles (Vanhercke et al, 2013(Vanhercke et al, , 2014El Tahchy et al, 2017) that strongly relied on an efficient use of the agroinfiltration-based system. The technology is continuously being upgraded by further cycles to create tailor-made products for biofuel applications (Reynolds et al, 2015;Reynolds et al, 2017), and is also being transferred to a range of major crops such as sugarcane (Zale et al, 2016), maize (Alameldin et al, 2017) and Sorghum bicolor (Vanhercke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco ( N. tabacum and N. benthamiana ) has served as the most common platform for producing oil in vegetative tissues given its ability to produce high biomass. DGAT1 has been used to boost oil in leaf or/and stem of tobacco through overexpression of DGAT1 alone (Andrianov et al, ; Wu et al, ) or in combination with one or more cDNA encoding proteins/enzymes such as acyl‐CoA:monoacylglycerol acyltransferase, WRI, oleosin, cysteine‐oleosin, and thioesterase (Chen et al, ; El Tahchy et al, ; Kelly et al, ; Petrie et al, ; Vanhercke et al, , ; Winichayakul et al, ). The latter multigene strategies have proven to be more effective in green tissues for enhancing the carbon flux into TAG at multiple metabolic levels, including upregulation of fatty‐acid biosynthesis (“Push”; e.g.…”
Section: Introductionmentioning
confidence: 99%